A rare extra scrotal spermatocele: a rare case presentation - Ansari, Sharique; Shaikh, Tanveer Parvez; V.U., Thahir; Mandhane, Nisha; Deolekar, Sandesh; Karandikar, Sangram; Singh, Shipra (International Journal of Research in Medical Sciences, 2017)
Right Inguinal region pain is a common complaint evaluated in surgical department. The number of differential diagnoses is lowered when the pain in a male patient is associated with a palpable tender mass. These diagnoses include inguinal hernia, inflamed inguinal lymph node, rectus sheath hematoma, cryptorchidism, mass derived from the spermatic cord, and polyorchidism. Right Inguinal region mass and pain caused by a spermatocele are unusual. Here we report a case of extra scrotal spermatocele causing right Inguinal region swelling and pain. To our knowledge this is a second reported case.